Answer:
2x + 3y = 42
Explanation:
Standard form should be like:
=> ax + by = c
To make an equation like the above one, we need to do the point-slope form first.
=> y - y1 = slope (x - x1)
Slope = -2/3
Y-intercept -> to find the y-intercept, we need to make the 'x' as 0.
=> y = -2/3 * 0 + 7
=> y = 7
X-intercept -> to find the x-intercept, we need to make 'y' as 0.
=> 0 = -2/3x + 7
=> -7 = -2/3x
=> -21/2 = -x
=> -10.5 = -x
=> 10.5 = x
So, x and y intercepts are 10.5 and 7.
We can now write the point-slope form:
=> y - 7 = -2/3 (x - 10.5)
=> y - 7 = -2/3x + 21/3
=> y = -2/3x + 7 + 7
=> y = -2/3x + 14
=> 2/3x + y = 14
=> Multiply all numbers by 3
=> 2x + 3y = 42